MENYOAL FILOSOFI ‘AN TARADIN PADA AKAD JUAL BELI (Kajian Hukum Ekonomi Syariah dalam Transaksi Jual Beli) - Abdur Rohman (Universitas Trunojoyo Madura, 2018)
Islam is a religion that is universal and comprehensive. Universal means that Islam is for all of mankind on earth and can be applied in every time and place until the end of time. Comprehensive means that Islam has a complete and perfect doctrine (syumul). Perfection teachings of Islam, because Islam regulates all aspects of human life, not just the spiritual aspect (pure worship), but also aspects mu'amalah covering economic, social, political, legal, and so on. As a comprehensive doctrine, includes three basic teachings of Islam, the faith, Shari'ah and morals. Relations between aqidah, Shari'ah and morality in the Islamic system is established such that it is a comprehensive system. Islamic Sharia divides into two, namely worship and mu'amalah. Included in the study mua'amalah is selling that put forward the principle of